Influence of the microstructural homogeneity on the high-temperature oxidation behavior of a single crystalline Ni-base superalloy - Pistor, Julian; Hagen, Sebastian; Virtanen, Sannakaisa; Körner, Carolin (Scripta Materialia, 2022)
Additive manufacturing by means of selective electron beam melting (SEBM) was recently demonstrated as an intriguing technique for the generation of single crystalline (SX) CMSX-4, a commercial Ni-base superalloy. The objective of this study is to compare the high-temperature oxidation resistance of SX SEBM-samples to their conventional counterparts which are derived by Bridgman investment casting. Therefore, time-resolved isothermal gravimetric analysis (TGA) was conducted at 850 and 1050 °C in synthetic air for 100 h. Due to solution annealing prior to oxidation, solidification induced elemental segregations could be homogenized completely in case of the SEBM-material, whereas they remained apparent for the conventional Bridgman samples. With residual elemental segregations inhomogeneous oxide scales emerged during exposure, exhibiting above-average scale thicknesses upon dendritic regions. Consequently, TGA revealed a higher mass gain in case of present segregations. In conclusion, a better high temperature oxidation resistance is observed for the homogeneous SEBM material.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Dendritic segregations; High-temperature oxidation; Ni-base superalloy; Protective scales; Selective electron beam melting (SEBM)